Nature, Socioeconomics and Adaptation to Natural Disasters : New Evidence from Floods - Ferreira, Susana; Hamilton, Kirk; Vincent, Jeffrey R. (2012)
The authors analyze the determinants of fatalities in 2,194 large flood events in 108 countries between 1985 and 2008. Given that socioeconomic factors can affect mortality right in the aftermath of a flood, but also indirectly by influencing flood frequency and magnitude, they distinguish between direct and indirect effects of development on flood mortality. The authors find that income is negatively associated with the frequency of floods and, conditional on their magnitude, the fatalities they cause in developing countries. However, for developed countries they find that increased income is associated with more fatalities, both directly (conditional on flood occurrence and magnitude) and indirectly through an increase in the frequency and magnitude of flood events. Also in contrast to the literature, they find that the effect of governance on flood frequency and fatalities in developing countries is U-shaped, with improvements in governance reducing the numbers of floods and deaths when governance is weaker but raising them when governance is stronger.